Legumes as Food Ingredient Characterization, Processing, and Applications - Clemente, Alfonso; Jimenez-Lopez, Jose C. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Legume crops provide a significant sources of plant-based proteins for humans. Grain legumes present outstanding nutritional and nutraceutical properties as sources of bioactive components with benefits in human health, while they are affordable food that contributes to achieving future food and feed security. Furthermore, they are major ingredients in the Mediterranean diet, playing a vital role in developing countries. Global food security requires a major re-focusing of plant sciences, crop improvement and production agronomy towards grain legumes (pulse crops) over coming decades, with intensive research to identify cultivars with improved grain characteristics, helping to develop novel legume-derived products (foods) adapted to today consumer preference. In this context, studies dealing with legume processing impact such as soaking, boiling, microwave cooking, germination, and fermentation among others, in their nutritional and anti-nutritional (i.e., food allergy) properties are of great interest in these future food developments. This Research Topic aims to bring together a collection of studies for a better understanding of current research in legume seed compounds functional properties to provide an updated and global vision of the importance of legumes in human health.